2021
DOI: 10.1590/1413-81232021266.1.43952020
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura da Estratégia Saúde da Família no Brasil: o que nos mostram as Pesquisas Nacionais de Saúde 2013 e 2019

Abstract: Resumo O artigo analisa a evolução da cobertura da Estratégia de Saúde da Família (ESF), a partir dos resultados dos inquéritos populacionais das Pesquisas Nacionais de Saúde (PNS) de 2013 e 2019. Foram calculados indicadores de cobertura de moradores e domicílios por Unidade de Saúde da Família (USF), frequência da visita de Agente Comunitário de Saúde (ACS), serviço de procura regular e tipo de serviço buscado; estratificados por área rural e urbana, grandes regiões, unidades da federação, escolaridade do re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
39

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 28 publications
1
32
0
39
Order By: Relevance
“…Previous research has found that lower use of SUS in certain regions was associated with higher private health insurance ownership [35,39]. The southeastern region has the lowest FHS coverage in the country [15] and the highest private health insurance ownership [33]. FHS coverage in the center-west region varies greatly between states [15], and its private health insurance ownership rate is slightly higher than the national rate [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found that lower use of SUS in certain regions was associated with higher private health insurance ownership [35,39]. The southeastern region has the lowest FHS coverage in the country [15] and the highest private health insurance ownership [33]. FHS coverage in the center-west region varies greatly between states [15], and its private health insurance ownership rate is slightly higher than the national rate [33].…”
Section: Discussionmentioning
confidence: 99%
“…The southeastern region has the lowest FHS coverage in the country [15] and the highest private health insurance ownership [33]. FHS coverage in the center-west region varies greatly between states [15], and its private health insurance ownership rate is slightly higher than the national rate [33]. Possible explanations for our results would be (a) private health insurance with better service coverage makes private insurance owners more loyal to private care; and (b) well-developed primary care in some center-west states and/or secondary care in the southeast has led to more loyalty to public care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ESF é o principal modelo de Atenção Primária à Saúde (APS) em consonância com os princípios do Sistema Único de Saúde (SUS): universalidade, integralidade e equidade. A importância dela é evidenciada pela cobertura de aproximadamente 131 milhões de brasileiros, agindo através da orientação comunitária, que faz a prevenção, vigilância, rastreamento e acompanhamento de casos, assim como a identificação de contatos e população vulnerável (Giovanella et al, 2021).…”
Section: Introductionunclassified
“…Pautava-se pela reformulação do objeto da saúde que, desde as bases do materialismo histórico, pretendia superar o biologicismo nas formas de lidar com a saúde e a doença (Lemos, 2018;Giovanella et al, 2021).…”
Section: Introductionunclassified